FIRST RECORD OF ‘Hemiancistrus’ punctulatus CARDOZO & MALABARBA, 1999 FOR URUGUAY (SILURIFORMES: LORICARIIDAE) - Serra Alanis, Wilson Sebastián; Scarabino, Fabrizio; Wlodek, Sabina; Furtado, Giovanni; Balao, Andrés (Boletín de la Sociedad Zoológica del Uruguay, 2020)
A recent expedition to lower Yaguarón river basin in northeastern Uruguay, revealed the presence of the loricariid catfish ‘Hemiancistrus’ punctulatus Cardozo & Malabarba, 1999, which represents the first record of this species for the country. We propose it as an endangered species for Uruguay considering its restricted distribution.